THE EFFECT OF INFLUENCER CREDIBILITY, CONTENT MARKETING AND E-WOM ON SKINTIFIC SKINCARE PURCHASE DECISIONS ON TIKTOK - Tri Rizky Suparman, Amelia; Sugianti, Rosita; Puji Astuti, Ramlah (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze the influence of influencer credibility, content marketing, and electronic word of mouth (e-WOM) on purchasing decisions for Skintific skincare on TikTok. The research method used is a quantitative approach with data collection through questionnaires distributed to respondents who have been exposed to Skintific promotions on TikTok. Data were analyzed using multiple linear regression. The results of the study indicate that influencer credibility has a significant effect on purchasing decisions, where the expertise, honesty, and attractiveness of influencers increase consumer trust. Interesting and educational content marketing also contributes to increasing purchasing interest, while e-WOM in the form of reviews and recommendations strengthens purchasing decisions. The conclusion of this study is that companies need to choose credible influencers, develop more engaging content marketing strategies, and encourage positive interactions through e-WOM in order to increase consumer purchasing decisions.